2018
DOI: 10.1021/acsomega.8b01808
|View full text |Cite
|
Sign up to set email alerts
|

Novel β-CD@ZIF-8 Nanoparticles-Doped Poly(m-phenylene isophthalamide) (PMIA) Thin-Film Nanocomposite (TFN) Membrane for Organic Solvent Nanofiltration (OSN)

Abstract: Organic solvent nanofiltration (OSN) membranes are always troubled by the “trade-off” effect between solvent flux and solute rejection. Hence, a rapid, convenient, and effective way to synthesize novel β-cyclodextrin-enhanced zeolite imidazole framework-8 (β-CD@ZIF-8) nanoparticles was first proposed and the nanoparticles were doped into both selective layer and poly(m-phenylene isophthalamide) support for fabricating thin-film nanocomposite membranes. Transmission/scanning electron microscopy images and X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 62 publications
(101 reference statements)
1
15
0
Order By: Relevance
“…The membrane showed a good pure water flux, good NaCl interception rate and excellent mechanical properties. The hydrophilic ZIF-8 modified PSF ultrafiltration membrane was prepared by Xu et al 31 The results indicated that ZIF-8 greatly enhanced the permeability and anti-pollution performance of PSF membrane. Efficient removal of nickel (II) from high salinity wastewater by a novel PAA/ZIF-8/PVDF composite ultrafiltration membrane was fabricated by Yang et al 32 The resulted membrane has the highest adsorption capacity to high salt wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane showed a good pure water flux, good NaCl interception rate and excellent mechanical properties. The hydrophilic ZIF-8 modified PSF ultrafiltration membrane was prepared by Xu et al 31 The results indicated that ZIF-8 greatly enhanced the permeability and anti-pollution performance of PSF membrane. Efficient removal of nickel (II) from high salinity wastewater by a novel PAA/ZIF-8/PVDF composite ultrafiltration membrane was fabricated by Yang et al 32 The resulted membrane has the highest adsorption capacity to high salt wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Surface hydrophilicity was reflected by 180‐s dynamic water contact angle (DCA, θ ) curves, which were estimated by a metre (JC2000A, Shanghai Zhong Cheng, China) …”
Section: Methodsmentioning
confidence: 99%
“…Several adjustable parameters were identified such as the concentration of PMIA in support, the contents of aqueous and organic phases, and the dosage of β ‐CD@ZIF‐8 nanoparticles to improve membrane performance. [ 233 ] Navarro et al. reported a novel procedure for positioning a monolayer of hydrophilic MIL‐101(Cr) nanoparticles in TFN membranes.…”
Section: Environmental Sectormentioning
confidence: 99%
“…to improve membrane performance. [233] Navarro et al reported a novel procedure for positioning a monolayer of hydrophilic MIL-101(Cr) nanoparticles in TFN membranes. As described in Figure 24, it was achieved by transferring a Langmuir-Schaefer (LS) film of MIL-101(Cr) between a top polyamide thin layer and a bottom cross-linked asymmetric polyimide (P84) support.…”
Section: Solvent Recoverymentioning
confidence: 99%